Regeneration changes in tree species abundance, diversity and structure in logged and unlogged subtropical rainforest over a 36-year period - Kariuki, M.; Kooyman, R.; Smith, R.; Wardell-Johnson, Grant; Vanclay, J. (Elsevier, 2006)
The long-term effects of logging treatments on rainforest regeneration are difficult to quantify due to compounding interactions with natural dynamics, site characteristics and tree species. The aim of this study was to examine regeneration differences over a 36-year period in stands subjected to various levels of disturbance ranging from natural, through an increasing intensity of individual tree removal to intensive logging. Multivariate and univariate analyses of trees 10 cm diameter at 1.3 m above the ground (dbh) showed that regeneration responses were generally correlated with disturbance gradient. In the undisturbed controls there were gradual changes that had no significant effects on tree species richness and diversity, stem density, or diameter distribution. Gradual changes were also observed during the early stages of regeneration following logging. However, in logged sites changes in tree species richness and diversity, stem density and diameter distribution became more rapid with time, and significant changes were observed. Similar regeneration events across site and disturbance levels resulted in three identifiable stages. In the first stage, lasting about 10 years, stem density of abundant shade tolerant trees decreased with no discernable changes in tree species richness. In the second stage, also lasting about 10 years, tree species richness and diversity, as well as stem density decreased to minima due to localised species turnover and net mortality. In the third stage, recruitment surpassed mortality and reversed the net loss of both species and stems, as tree species assemblages began to return to pre-disturbance levels.Sites subjected to individual tree selective logging returned to their pre-logging states in all aspects within 35 years of logging, but diameter distribution of trees ≥40 cm dbh showed low density compared to that observed in the controls. After 15-30 years, sites subjected to more intensive logging returned to their pre-logging levels of stem densities, species abundance and richness, but after 35-44 years of regeneration this sites had low species diversity and high densities of both the small sized stems and shade intolerant treespecies. More intensively logged sites also had a low density of shade tolerant tree species compared to the controls. This suggests that the restoration of forest structure takes considerably longer than the restoration of tree species richness and abundance following logging in these forests. A high rate of stand basal area growth and a modest diameter distribution of lager trees ≥40 cm dbh were observed in moderate tree selection logging. This indicates high timber production potential at moderate tree selection rate in this type of forest. However, if the stem size distribution of larger trees is to be maintained, a logging cycle longer than 50 years is necessary.